Study Of Hypothyroidism In Metabolic Syndrome (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Metabolic syndrome (MetS) is a combination of risk factors that could raise the risk of cardiovascular disease, diabetes and death. Several studies have demonstrated a correlation between thyroid function and MetS indices. The present study was designed to study hypothyroidism in metabolic syndrome.Aims and objectives: To study co-relation of hypothyroidism with central obesity, triglyceride level, hypertension, fasting blood sugar.Materials and methods: This cross-Sectional study was conducted in the Department of General Medicine, Santosh medical college and hospital, Ghaziabad, Uttar Pradesh. In a semi-structured fashion, weight and waist circumference were noted. The fasting blood sugar was done by the enzymatic calorimetric method using semi auto analyzer. The high-density lipoprotein cholesterol and triglycerides were done enzymatically on fully automated clinical chemistry analyzer. The thyroid hormone assay was done by ChemiluminescenceImmuno Assay.Results: The prevalence of hypothyroidism was higher among increased high risk central obesity (50%) than high risk (27.5%) and low risk (7.3%). The prevalence of hypothyroidism was higher among hypertensive patients (31%) than non-hypertensive (13.8%). Five MS criteria was fulfilled among 40% patients. The prevalence of hypothyroidism was higher among whom MS criteria was five (32.5%) than three (17.1%) and four (8%). There was significant (p=0.04) association of prevalence of hypothyroidism with central obesity, MS criteria fulfilled, and hypertension.Conclusion: We found a significant association of prevalence of hypothyroidism with central obesity, hypertension, and MS criteria fulfilled.